If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -3x + -7 = 11 Reorder the terms: -7 + 12x + -3x = 11 Combine like terms: 12x + -3x = 9x -7 + 9x = 11 Solving -7 + 9x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 9x = 11 + 7 Combine like terms: -7 + 7 = 0 0 + 9x = 11 + 7 9x = 11 + 7 Combine like terms: 11 + 7 = 18 9x = 18 Divide each side by '9'. x = 2 Simplifying x = 2
| 56-s=45-9 | | 1+(3*7)=z | | 1+(3*7)= | | 1/2-1=1/44 | | -24p^2q^2+(-2pq)+3= | | 2x-6x+21=-13 | | -4x+21=-13 | | 28x+4+7x+7=102 | | 1xy=78 | | 1*y=787 | | 1y=78 | | xy=-40 | | ax+5x-4=10 | | 4-4x^2+4xy-y^2= | | 15-1/2x=1/4x | | x/5-x/3=8/15 | | 5/8+(-7/12) | | -4/7+2/7 | | 4x-7y=29 | | 5/21x=2/3x-1/7 | | 2(3x-1)=5(2-7x) | | 3-x=2x+18 | | 2x+15=0 | | x+(0.2746x)=866.73 | | x+(0.2746x)=1000 | | 2abc+3a+4b= | | 2w+2(2w+1)=42 | | 1/3+5/12x=3/4 | | 4/3x+1=21 | | 5y+37=20+9y | | -5(6-3c)=7c+2 | | -3(4+r)=9 |